ANALISIS PEMBIAYAAN BANK SYARIAH DAN INSTRUMEN MONETER SYARIAH TERHADAP STABILITAS MONETER DI INDONESIA - Lucky, Muhammad (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2024)
This study aims to analyze the effect of Islamic monetary instruments and financing on monetary stability in Indonesia. This research uses Vector Error Correction Model (VECM), Granger Causality Test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) by first conducting stationarity test, cointegration test, optimum lag test. The data used in this study are monthly secondary data from the variables of Money Supply (M2), Sharia Bank Indonesia Certificates (SBIS), Sharia Interbank Money Market (PUAS), State Sharia Securities (SBSN), Islamic Banking Financing and Ijarah Financing. Based on the period 2015-2021 with time series data. The results of the VECM Model research show that in the long run the variable instruments SBIS, PUAS, SBS, Islamic Banking Financing and Ijarah Financing have a significant but negative effect on the Money Supply (M2).